Aerial Spray Drift – Consequences of Spraying Small Droplets of Herbicide. (1st August 2014) - Matthews, Graham
Since 2000, aerial application of the herbicide glyphosate has been used to control illicit coca (Erythroxylum coca) and poppy (Papaver somniferum) crops in Colombia as part of the campaign to curb illegal drugs at their source. Pilots were directed to spray individual areas of coca, which were small and surrounded by other crops or forest. These farms were distributed over large areas of Colombia. In some of these areas, Colombian authorities had managed to persuade many farmers who had grown coca to switch to other crops. Where the coca was grown in the southern part of Colombia, in Putumayo and Narino provinces, spray not only affected vegetation in areas of Colombia, it was also alleged by some that it had a detrimental effect on farms along the Ecuador border in Esmeraldas and Sucumbios provinces to the west and east of the Andes. The Ecuador government requested a buffer zone to protect their farmers and rich diverse natural forests. Colombia agreed temporarily to suspend spraying within 10 km of the border with Ecuador in 2005, but the extent to which this agreement was observed is uncertain. Consequently, a lawsuit was brought by Ecuador before the International Court of Justice in 2008. The case was removed by Ecuador in September 2013 when Colombia agreed "inter alia, an exclusion zone, in which Colombia will not conduct aerial spraying operations, creates a Joint Commission to ensure that spraying operations outside that zone have not caused herbicides to drift into Ecuador and, so long as they have not, provides a mechanism for the gradual reduction in the width of the said zone; and whereas, according to the letters, the Agreement sets out operational parameters for Colombia's spraying programme, records the agreement of the two Governments to ongoing exchanges of information in that regard, and establishes a dispute settlement mechanism". With the importance of protecting the environment, this paper examines the published data on the technical aspects of the spray programme and confirms that under the weather conditions in the Andean area, spray drift and deposition over greater distances than predicted initially by a Spray drift model AgDISP occurred.